From "Buzzword" to Best Practice: Applying Intersectionality to Children Exposed to Intimate Partner Violence. (January 2018) - Etherington, Cole; Baker, Linda
Empirical studies on the impact of intimate partner violence (IPV) on children have burgeoned over the last three decades. Notably absent from existing approaches to studying children exposed to IPV, however, is attention to how various positionalities intersect to impact the experiences of children and their families. In fact, while the importance of an intersectional framework for understanding IPV has been discussed for over two decades, little or no attention has been given to issues of children's exposure to IPV. In this article, we examine the current state of the literature on children exposed to IPV through an exploratory meta-analysis, finding limited application of intersectionality and a focus on discrete categories of difference. We then demonstrate why and how an intersectional framework should be applied to children exposed to IPV, with specific strategies for research and policy. We suggest a child-centered approach that recognizes diversity among children exposed to IPV, extending the challenge to traditional "one-size-fits-all" models to include an intersectionality-informed stance.